DAMPAK PEMBELAJARAN DARING DAN PSHYCAL DISTANCING TERHADAP TINGKAT KECEMASAN MAHASISWA KEBIDANAN STIKES MUHAMMADIYAH SIDRAP ERA COVID-19 - St. Hasriani; Nurhidayah Nurhidayah (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2021)
Covid-19 in a short time spread to almost all countries in the world, including Indonesia. The impact of Covid-19 is very dangerous, in Indonesia taking preventive steps, namely Pshycal distancing is a policy that has an impact on decisions regarding online learning. This policy is to minimize and suppress the spread of Covid-19. Studying online is not easy. Difficulties arise not only in terms of skill in using technology, but by adding a large quota and not having a laptop. This research aims to determine the impact of online learning and Pshycal distancing on the anxiety level of midwifery students. The method used is descriptive with a quantitative approach. The population in this study were the midwifery students of STIKES Muhammadiyah Sidrap. Sampling was done by random sampling. The criteria for the sample were midwifery students who were still active and following online learning. ZSAS research instrument. The research questionnaire uses Google Form through online media. Dianalisi using the Chi-Square test to determine the relationship between the two variables. Data analysis was performed using SPSS Version 24.0. The results of the analysis show that online learning carried out at STIKES Muhammadiyah Sidrap was obtained by students who did not agree with online learning (83.3%) because of obstacles in using learning applications, namely students did not have a quota (47.9%) and difficult Internet networks (41.7%). While students tend to experience severe anxiety (50.0%) and moderate (29%) It can be concluded that there is an effect of online learning and Pshycal distancing on student anxiety. Criticism can appear in various stages of lectures, so it is important for research related to differences in the degree of anxiety of early and late students.